Pengaruh Financial Technology, Locus of Control, dan Orientasi Kewirausahaan Terhadap Kinerja Keuangan UMKM(Survey pada UMKM Jamu di Kecamatan Nguter Tahun 2023) - Kristanto Saputra, Bayu; Wibowo, Edi (PENG: Jurnal Ekonomi dan Manajemen, 2025)
In the context of the Indonesian economy, small and medium enterprises (MSMEs) play a very crucial role, both in absorbing labour (more than 90%) and contributing to the national Gross Domestic Product (GDP) (more than 50%). This study aims to examine the significance of financial technology, locus of control, and entrepreneurial orientation on the financial performance of herbal medicine MSMEs operating in Nguter Sub-district. Quantitative data obtained directly from respondents is the main source in this study. All herbal MSMEs totalling 63 units in Nguter Sub-district became the population as well as the sample in this study. Data analysis was conducted through several stages, including the classical assumption test, multiple linear regression, t-test, F-test, and calculation of the coefficient of determination (R-squared). The results of the analysis show that the use of financial technology has a positive and significant influence on the financial performance of herbal MSMEs in Nguter Sub-district. However, the locus of control variable only has an insignificant positive effect on the financial performance of herbal MSMEs, while entrepreneurial orientation has a negative effect which is also insignificant.